Rescuing Our Roots : The African Anglo-Caribbean Diaspora in Contemporary Cuba - Queeley, Andrea (Book collections on Project MUSE., 2015)
Andrea Queeley examines the interconnections between blackness, inequality, migration, and Diaspora in the wake of the effects of the collapse of the Soviet Union on Cuba. Rescuing Our Roots shows, via ethnography, how black Anglophone Caribbean people's desire for social mobility, political engagement, and the opportunity for a better economic situation operates alongside ideas about respectability.